2008
DOI: 10.1128/aac.00102-08
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Daptomycin Pharmacodynamics and Resistance at Various Dosage Regimens against Staphylococcus aureus Isolates with Reduced Susceptibilities to Daptomycin in an In Vitro Pharmacodynamic Model with Simulated Endocardial Vegetations

Abstract: The need to investigate novel dosing regimens and combinations is essential in combating poor treatment outcomes for Staphylococcus aureus bacteremia and endocarditis. We evaluated the impact of simulated standard-and high-dose daptomycin in combination with gentamicin or rifampin against daptomycin-susceptible and nonsusceptible matched strains of S. aureus. These strains were collected from the daptomycin bacteremia and endocarditis clinical trial and consisted of three susceptible strains (MIC, 0.25 mg/lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
89
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(103 citation statements)
references
References 28 publications
12
89
0
Order By: Relevance
“…In a retrospective cohort study of VRE bloodstream infections, treatment with daptomycin or linezolid demonstrated no difference in mortality; however, infection with E. faecium and concurrent treatment with rifampin or gentamicin were independent risk factors for mortality (54). Antagonistic activity is often observed when rifampin is added to bactericidal agents in high-inoculum infections, due to high rates of mutations conferring resistance (ϳ1 in 10 6 ) (31,55,56). The in vitro model demonstrated antagonism with rifampin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective cohort study of VRE bloodstream infections, treatment with daptomycin or linezolid demonstrated no difference in mortality; however, infection with E. faecium and concurrent treatment with rifampin or gentamicin were independent risk factors for mortality (54). Antagonistic activity is often observed when rifampin is added to bactericidal agents in high-inoculum infections, due to high rates of mutations conferring resistance (ϳ1 in 10 6 ) (31,55,56). The in vitro model demonstrated antagonism with rifampin.…”
Section: Discussionmentioning
confidence: 99%
“…As described previously, organism stocks containing approximately 10 10 CFU/ml were prepared by inoculating 5-ml test tubes of normal saline with colonies harvested from fresh overnight growth on TSA (20,22,24,31,32). Simulated endocardial vegetations (SEVs) containing 10 9 CFU/g were prepared by combining 0.05 ml of the organism suspension with 0.4 ml of human cryoprecipitated antihemolytic factor (AHF) from volunteer donors (Rhode Island Blood Bank, Providence, RI), 0.05 ml of an aprotinin suspension, and 0.025 ml of a platelet suspension (platelets mixed with normal saline; 250,000 to 500,000 platelets per clot) in 1.5-ml Eppendorf tubes.…”
Section: Methodsmentioning
confidence: 99%
“…In cases of primary treatment failure with S. aureus infections, rifampin has been recommended as an adjunctive therapeutic agent (3). Studies with in vitro and in vivo pharmacodynamic models of biofilm-associated infection support the use of daptomycin in combination with rifampin, where synergistic activity has been associated primarily with preventing the emergence of daptomycin-nonsusceptible strains (4)(5)(6). We have recently reported a high rate of success with daptomycin in combination with rifampin for treatment of complicated bone and joint infections (7), and in this study, we report the relationship between treatment outcome and in vitro synergy with complex deep MRSA infections.…”
mentioning
confidence: 99%
“…Daptomycin in combination with adjunctive antibiotics, such as rifampin, aminoglycosides, or co-trimoxazole, may improve antimicrobial killing or inhibit the emergence of resistance compared to daptomycin alone (5,14). New Infectious Diseases Society of America (IDSA) guidelines for the treatment of prosthetic joint infections recommend combining rifampin with primary therapy (15), but published clinical experiences with daptomycin combined with rifampin have been very limited.…”
mentioning
confidence: 99%
“…50,51 In vitro pharmacodynamic modelling with simulated endocarditis vegetations has demonstrated rapid bactericidal activity with daptomycin-susceptible strains, with more rapid killing at a dose of 10 mg/kg. 52 These authors reported an improvement in activity with combination regimens against some, but not all, isolates, and suggest that in the presence of strains with reduced susceptibility high-dose daptomycin or combination therapy may be a reasonable treatment option. Cunha et al have reported a successful clinical outcome using high-dose (12 mg/kg) daptomycin after continuing bacteraemia and mitral valve IE following 10 days of daptomycin (6 mg/kg) in combination with linezolid (600 mg 12 h).…”
mentioning
confidence: 99%